Understanding the Costs of Deflation in the Japanese Context - Baig, Taimur (IMF Working Papers; Working Paper, 2003)
This paper examines the cost of deflation in the context of Japan's ongoing deflationary episode. The impact of deflation owing to the zero interest rate bound on monetary policy, wage rigidity, redistribution of wealth from debtor to creditor, and inflexibilities in the financial sector are examined. It is seen that the generalized decline in the Japanese price level, however gradual or mild, has substantially exacerbated the economy's adjustment process under already difficult economic conditions.